Selling spirituality : the silent takeover of religion - Carrette, Jeremy R. (Routledge, 2005)
Selling Spirituality shows how spirituality today functions as a powerful commodity in the global marketplace, promising to soothe away the ills of modern life whilst functioning as a silent form of economic, cultural and political restraint.